Dental caries experience among 15-year-old adolescents in north-west Russia - Gorbatova, Maria A.; Gorbatova, Lyubov N.; Grjibovski, Andrej (University of Oulu, 2011)
To estimate the prevalence and experience of dental caries among 15-year-old adolescents in north-west Russia between 2007 and 2008. Study design. A cross-sectional study. In total, 352 adolescents at the age of 15 were selected at random from 3 urban and 4 rural areas in the Arkhangelsk region. Girls comprised 53.4% of the sample. Caries experience was assessed at D3 level by a single calibrated examiner and was estimated as a sum of decayed, missing and filled teeth (DMFT). The prevalence of caries was 91.8% with a mean DMFT of 4.92. On average, there were 2.61 decayed, 0.13 missing and 2.18 filled teeth per participant. No gender differences in the prevalence of caries in any of the settings or in the full sample were observed. In urban areas, the average number of decayed teeth was lower (2.15 vs. 2.95, p=0.006), while the number of filled teeth was greater (2.71 vs. 1.79, p<0.001) than in rural areas. Under assumption of the representativeness of the sample, no improvements in the overall caries prevalence among 15-year-old children in the Arkhangelsk region occurred since 1997–1998. Urban-rural variations, but not gender variations, in caries experience were observed. The levels are considerably higher than those in neighbouring Nordic countries and the Russian average. Urgent public health measures on both population and individual levels are needed to improve the situation.